INCREASE THE EFFICIENCY OF TECHNICAL SERVICES IN MOTOR TRANSPORT ENTERPRISES - Abdukarim Muxtorov (Journals Park Publishing, 2022)
This article analyzes the measures to further improve the system of Organization of the provision of existing transport services in the Republic, the plan of measures such as maintenance and repair of cars, storage, side lubrication and increasing the number of motor-transport enterprises, which include the provision of spare parts, the implementation of technological equipment, reconstruction and improvement of existing motor-transport enterprises.
Keywords: Motor transport; enterprises; maintenance